STRUKTUR JAPPIH PA’BURA MASYARAKAT BUGIS WAJO’ DESA KUALA DUA KABUPATEN KUBU RAYA - Rahmah Rahmah; Parlindungan Nadeak; Agus Wartiningsih (Universitas Tanjungpura, 2021)
AbstractThe research used a descriptive method in form of qualitative research. The structural approach applied in this research, the technique of data collection included observation, interview, and note-taking. The tool of the data collection was the researcher acted as the key instruments helped by the observation checklist, interview guidelines, notes, and recorder. The data came from Jappih Pa’bura the Bugis Wajo community in Desa Kuala Dua, Kabupaten Kubu Raya. The data of the research was in form of words, phrases, sentences, perseverance, triangulation, and the scope of references. The data consisted of 30 spells within poetry structural analysis (poetry method). The result of the research showed there were diction, assessment, concrete words, sounds (rhythm and rhyme). The result of this research will merge with the lesson plan of Bahasa Indonesia in eight-year students of Junior High School in Kurikulum 2013 KD 3.10, investigating the structure of the poetry and the language of local poetry that had to be read and listened to. KD 4.10 the expression of ideas, feeling, and messages in form of spoken and written folk poetry within the structure, rhyme, and the use of language.Keywords: Structure, Bugis Jappih Pa’bura Community